The Online Gaming Behaviour of University Students Undergoing Self-Quarantine - Fahrizal, Yanuar; Wati, Anisa Risma; Sutarjo, Puji; Martin, Neil M (Fakultas Ilmu-ilmu Kesehatan, 2023)
Self-quarantining is one of the coping mechanisms used during the pandemic. However, it can negatively affect the sufferer. Self-quarantine causes many students to play online games excessively. Understanding students' online game behavior during self-quarantine can help to prevent online game addiction and encourage positive self-quarantine activities. This study aims to investigate the online gaming experience during self-quarantine for university students who tested positive for COVID-19 during the pandemic. Phenomenological qualitative research was used. The study’s sample consists of ten university students from Yogyakarta who tested positive for COVID-19 and played online games during self-quarantine. Purposeful sampling was utilized, and data were collected through semi-structured in-depth interviews. The Colaizi method was then used to analyze the data. The results indicated four themes: (1) the changes in online gaming behaviors before and after being tested positive for COVID-19; (2) the influencing factors on online gaming behavior before and during self-quarantine, (3) the impacts of parenting styles on online gaming behaviors, and (4) the impacts/consequences of online gaming behaviors. Overall, during self-quarantine, the students changed their behavior during online gaming, which was influenced by internal and external factors. They also became aware of the consequences of excessive online gaming